The Relationship between Climbing Ability and Physiological Responses to Rock Climbing. (4th December 2013) - Baláš, Jiří; Panáčková, Michaela; Strejcová, Barbora; Martin, Andrew J.; Cochrane, Darryl J.; Kaláb, Miloš; Kodejška, Jan; Draper, Nick
Abstract : Aim . The aim of this study was to examine the relationship between submaximal and maximal physiological responses to rock climbing for climbers of differing abilities. Methods . Twenty-six male climbers performed a submaximal climbing test on a known circuit at 90° (vertical) and 105° (15° overhanging) inclination and speed 25 movements·min −1 . A maximal test was undertaken on a similar circuit at the same speed with inclination increasing by 10° for each successive 3 min stage. Results . Mean oxygen consumption and heart rate (HR) increased with wall inclination and climbers reached a mean (±SD) peak V ˙ O 2 of 40.3 ± 3.5 mL·kg −1 ·min −1 during the maximal test. Self-reported climbing ability was negatively correlated with V ˙ O 2 and HR during the submaximal test at 90° (V ˙ O 2, r = − 0.82 ; HR, and r = − 0.66 ) and at 105° (V ˙ O 2, r = − 0.84 ; HR, and r = − 0.78 ) suggesting an increased exercise economy for climbers with a higher ability level. Conclusion . Findings from this study indicate that there is a relationship between wall inclination and the physiological demand of a climb. However, the increased technical ability and fitness of higher level climbers appears to an extent to offset the increased demand through improved exercise economy which in turn leads to an increased time to exhaustion and an improvement in performance.